Synthesis and properties of carbon quantum dots and their research progress in cancer treatment. (December 2021) - Lai, Chunmei; Lin, Simin; Huang, Xiaozhen; Jin, Yanqiao
Abstract: Carbon quantum dots (CQDs), a new type of fluorescence carbon nanomaterials with particle size varied from 2 to 10 nm, have attracted much attention due to their strong multi-color luminescence properties, unprecedented biocompatibility, excellent aqueous dispersibility and easy preparation from a wide range of carbon materials. These multiple attributes help CQDs possess a broad range of prospective applications in numerous fields, especially for bio-imaging, drug delivery, chemical probe and photon therapy because of their advantages of low cytotoxicity and good biocompatibility. Therefore, it is necessary to recap the synthesis and application of CQDs-based materials in the field of biomedicine. The methods for the synthesis of CQDs are introduced firstly, and then different performance of CQDs related to their applications are demonstrated and discussed, including the function tailoring of CQDs. Finally, future opportunities and challenges of CQDs-based materials in this burgeoning field are proposed from the perspective of the rational design of systematic CQDs-based materials toward the biomedicine field. Graphical abstract: Image 1 Highlights: CQDs acted as a fluorescent dye has emerged with great interest. The performances of CQDs in cancer treatment are discussed systematically. This review provides a practicable guidance for the design of advanced fluorescence CQDs. Future perspectives and challenges in practical application are also investigated.